Tribo-Electrochemistry of Post-CMP Cleaning: Results for Co and Cu Wafer Films Brushed in Different Solutions. (17th May 2021) - Johnson, C. A.; Liu, J.; White, M. L.; Roy, D.
Abstract : Optimization and evaluation of post chemical mechanical planarization cleaning (PCMPC) solutions rely on adequately understanding the electrochemical details of the cleaning interface. The present work addresses some of the essential facets of this task with laboratory scale tribo-electrochemical measurements using a selected set of solutions designed to post-CMP clean Cu (wiring) and Co (diffusion barriers/contacts) wafer films. The experiments employ an exploratory PCMPC formulation using citric acid, and two commercial solutions. The measurements, performed in a custom-built cell, both with and without brushing of the metal samples, yield detailed results for open circuit potential transients, corrosion currents/potentials, as well as the characteristic impedance parameters indicating surface cleaning efficiencies. The citrate data help to set up a comprehensive analytical framework for PCMPC characterization, which is further extended to assess the two commercial solutions. A comparative analysis of the data collected for brushed and unbrushed wafer films brings out the individual and synergistic cleaning functions of surface chemistry and tribology. The role of tribology is clearly observed as the cleaning efficiencies (determined using impedance spectroscopy) of all three solutions increase with the incorporation of brushing.